EFFECTS OF SOCIAL MOVEMENTS ON PUBLIC POLICY CYCLE - Carlos, Euzeneia; Dowbor, Monika; Albuquerque, Maria do Carmo (Universidade Federal da Bahia, 2021)
This comparative study involving the human rights, child and adolescent and health sectors analyzes the political effects of social movements on public policy cycle. The empirical research compares six campaigns over two decades (1990 and 2000), triggered by related social movements by means of documents and interviews with activists. We use a correlational approach to measure the political effects, that is, the correspondence between the campaign demands and the outcomes in sectoral politics. We classify the political effects associated with movement campaigns into the public policy cycle typology. Our main contribution is to show the influence of social movements in the different stages of the policy cycle, namely: agenda setting, specification of alternatives, decision, and implementation, whose effects are produced by conditions such as repertoires, coalitions, and state capabilities.